Pedagogical Strategies for English Composition Instruction Among Learners in Public Primary Schools Within the Igembe Central Sub-County, Kenya - Nyaga, Florence (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
In primary education, composition writing is crucial for English language development. It improves both speaking and writing skills, fosters critical thinking, and requires careful instruction. Factors influencing instruction effectiveness must be considered by educators. This research aimed to examine the impact of specific variables on the teaching of composition writing in public primary schools located in the Igembe Central Sub-County. The study objectives were to assess the effects of teaching methodologies employed in composition writing instruction and to ascertain the impact of student motivation on the teaching of English composition writing. The research was guided by Levi Vygotsky’s sociocultural theory and Noam Chomsky’s language acquisition theory. Employing a descriptive survey design, the study was conducted in the Igembe Central Sub-County, focusing on a target population of 7,011 individuals, including 171 class seven English teachers and 6,840 class seven pupils across 75 public primary schools. Utilizing the finite population formula, a sample size of 361 class seven pupils and 9 class seven English teachers was determined through simple random sampling where proportionate sampling ensured each sample size (teachers and pupils) was sampled independently. Data collection involved the use of interview schedules for English teachers and questionnaires for class 7 pupils, with questions designed to align with the study objectives to ensure instrument validity. A pilot study, conducted in a school resembling the study sample, assessed instrument reliability using Cronbach’s Alpha coefficient, achieving a threshold of 0.70. Collected data underwent cleaning, coding, and analysis using Statistical Package for Social Sciences (SPSS) version 26, employing descriptive statistics such as frequency and percentages, and hypothesis testing at a 95% level of significance using Chi-square. Finding indicated a significant and positive influence of teaching approach and pupil motivation on English composition writing instruction. Recommendations include English teachers adopting innovative teaching methods to enhance instruction, fostering pupil motivation, and head teachers providing support through the provision of instructional materials and incentives to encourage pupil engagement.